A Multicenter, Randomized, Double-Blind, Placebo-Controlled, Single-Dose, Phase III, Non-Inferiority Study Comparing PrabotulinumtoxinA and OnabotulinumtoxinA for the Treatment of Moderate to Severe Glabellar Lines in Adult Patients. (5th April 2019) - Rzany, Berthold-Josef; Ascher, Benjamin; Avelar, Rui L; Bergdahl, Jesper; Bertucci, Vince; Bodokh, Isaac; Carruthers, James Alastair; Cartier, Hugues; Delmar, Henry; Denfeld, Ralf; Gross, John E; Heckmann, Marc; et al.
Abstract: Background: PrabotulinumtoxinA is a 900-kDa botulinum toxin type A produced by Clostridium botulinum . Objectives: The authors sought to investigate the efficacy and safety of prabotulinumtoxinA compared to onabotulinumtoxinA and placebo for the treatment of glabellar lines. Methods: This was a 150-day, multicenter, double-blind, controlled, single-dose Phase III study. Adult patients (n = 540) with moderate to severe glabellar lines at maximum frown as assessed by the investigator on the validated 4-point Glabellar Line Scale (0 = no lines, 1 = mild, 2 = moderate, 3 = severe), who also felt that their glabellar lines had an important psychological impact, were enrolled. Patients were randomized 5:5:1 to receive a single treatment (0.1 mL injected into each of 5 glabellar sites) of 20 U prabotulinumtoxinA (n = 245), 20 U onabotulinumtoxinA (n = 246), or placebo (n = 49). The primary efficacy endpoint was the proportion of responders (patients with a Glabellar Line Scale score of 0 or 1 at maximum frown by investigator assessment) on day 30. Results: Responder rates for the primary efficacy endpoint were 87.2%, 82.8%, and 4.2% in the prabotulinumtoxinA, onabotulinumtoxinA, and placebo groups, respectively. The absolute difference between prabotulinumtoxinA and onabotulinumtoxinA groups was 4.4% (95% confidence interval [−1.9, 10.8]). Given that the lower bound of the 95% confidence interval for the difference was less than −10.0%, noninferiority of prabotulinumtoxinA vs onabotulinumtoxinA was concluded. Five patients (3 prabotulinumtoxinA, 1.2%; 1 onabotulinumtoxinA, 0.4%; 1 placebo, 2.0%) experienced serious adverse events, none of which were study drug related. Conclusions: A single treatment of 20 U prabotulinumtoxinA was safe and effective and noninferior to 20 U onabotulinumtoxinA for the treatment of moderate to severe glabellar lines. Level of Evidence: 1: